A Dynamic Co-expression Map of Early Inflorescence Development in Setaria viridis Provides a Resource for Gene Discovery and Comparative Genomics - Zhu, Chuanmei; Yang, Jiani; Box, Mathew S.; Kellogg, Elizabeth A.; Eveland, Andrea L. (Frontiers in Plant Science, 2018)
The morphological and functional diversity of plant form is governed by dynamic gene regulatory networks. In cereal crops, grain and/or pollen-bearing inflorescences exhibit vast architectural diversity and developmental complexity, yet the underlying genetic framework is only partly known. Setaria viridis is a small, rapidly growing grass species in the subfamily Panicoideae, a group that includes economically important cereal crops such as maize and sorghum. The S. viridis inflorescence displays complex branching patterns, but its early development is similar to that of other panicoid grasses, and thus is an ideal model for studying inflorescence architecture. Here we report detailed transcriptional resource that captures dynamic transitions across six sequential stages of S. viridis inflorescence development, from reproductive onset to floral organ differentiation. Co-expression analyses identified stage-specific signatures of development, which include homologs of previously known developmental genes from maize and rice, suites of transcription factors and gene family members, and genes of unknown function. This spatiotemporal co-expression map and associated analyses provide a foundation for gene discovery in S. viridis inflorescence development, and a comparative model for exploring related architectural features in agronomically important cereals.